Meyler's side effects of endocrine and metabolic drugs - Aronson, J. K (Elsevier, 2009)
Elsevier now offers a series of derivative works based on the acclaimed Meylers Side Effect of Drugs, 15th Edition. These individual volumes are grouped by specialty to benefit the practicing physician or health care clinician. Endocrine and metabolic diseases are common, includes diseases such as diabetes, thyroid disease, and obesity. Endocrinologists, including diabetes professionals, internal medicine and primary care practitioners, obstetricians and gynecologists, and others will find this book useful when treating endocrine or metabolic diseases.The material is drawn from the 15th edition of the internationally renowned encyclopedia, Meyler\'s Side Effects of Drugs, and the latest volumes in the companion series, Side Effects of Drugs Annuals. Drug names have usually been designated by their recommended or proposed International Non-proprietary Names (rINN or pINN); when those are not available, clinical names have been used. In some cases, brand names have been used.This volume is critical for any health professional involved in the administration of endocrine and metabolics mediations. Surpasses the Physician\'s Desk Reference © by including clinical case studies and independent expert analysisComplete index of drug namesMost complete cross referencing of drug-drug interactions availableExtensive references to primary and secondary literatureAlso includes information on adverse effects in pregnancyThe book is divided into eight sections:Corticosteroids and related drugsProstaglandinsSex hormones and related drugsIodine and drugs that affect thyroid functionInsulin and other hypoglycemic drugsOther hormones and related drugsLipid-regulated drugsEndocrine and metabolic adverse effects of non-hormonal and non-metabolic drugs
Keywords: metabolické nemoci; Endocrine System Diseases; Drug-Related Side Effects and Adverse Reactions; léčivé přípravky; nežádoucí účinky léčiv; farmacie a farmakologie; vnitřní lékařství; endokrinologie; Pharmaceutical Preparations; Metabolic Diseases; nemoci endokrinního systému